Prevalence and Structural Abnormal Findings of Injured Knee Joint among Adult Patients detected by Magnetic Resonance Imaging Study of 70 Cases in a tertiary hospital of Bangladesh (Journal of Current and Advance Medical Research, 2021)
Background: Magnetic resonance imaging is a very useful diagnostic tool for the detection of abnormalities of injured knee joint.Objective: This present study was performed to see the different abnormalities of injured knee joint detected by MRI among adult patients.Methodology: This cross-sectional study was conducted in the Department of Radiology and Imaging at Bangabandhu Sheikh Mujib Medical University (BSSMU), Dhaka, Bangladesh from January to June 2021 for a period of six months. The patients in the age group of equal or more than 18 years with both male and female who were visiting Department of Orthopaedics at BSMMU, Dhaka with history of knee injuries were subjected to MRI were selected as study population. MRI findings of the knee joint were analyzed for the presence of any signal changes or lesions of varying severity for the structures of menisci, cartilage, bone marrow, tendons and ligaments of injured knee joint.Results: A total number of 65 cases of knee joints were analyzed. The mean with the SD of age of the study population was 35.34±13.371. The left knee (60.0%) was more involved than right knee (40.0%). The lesion in femur and tibia were found in 10(15.4%) cases and 8(12.3%) cases respectively. Out of 65 knee joints there were 41 joints were found the tear of anterior cruciate ligament. The complete, interstial tear in the anterior cruciate ligaments were 26(40.0%) and 15(23.1%) knee joints respectively. However, anterior cruciate ligaments of 24(36.9%) knee joints were found normal. Medial meniscus (36.9%) was more involved than lateral meniscus (18.5%).Conclusion: In conclusion young adult male are more commonly affected their left knee joint with the tearing of complete tear of anterior cruciate ligaments and involvement of medial meniscus.Journal of Current and Advance Medical Research, July 2021;8(2):80-84